Inside ethnic families : three generations of Portuguese-Canadians - Noivo, Edite, 1951- (McGill-Queen's studies in ethnic history. Series 2., 1997)
"Inside Ethnic Families is a rich and lively ethnography that describes the perceptions, illusions, and life experiences of three generations of Portuguese-Canadians. Edite Noivo provides an insider's perspective on a number of family-related issues ranging from housework and aging to gender relations and family violence."--Jacket